(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article analyzes the notions of time and how they are reflected through ways of expressing the invariant part of language and speech. In particular, empirical and theoretical studies were used to study the important features of time concepts in the linguistic aspect, their reflection through ways of expressing the invariable part of language and speech